Reducing Warehouse Errors Using FMEA and Poka-Yoke at Bonded Logistics Center: Mengurangi Kesalahan di Gudang Menggunakan FMEA dan Poka-Yoke di Pusat Logistik Berikat - Elvi Anggino Erzon; Iriani Iriani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Warehouse operations play a critical role in maintaining supply chain continuity, particularly within bonded logistics centers subject to strict customs regulations. Specific Background At the bonded logistics center warehouse of PT XYZ, frequent operational errors in receiving and picking processes have resulted in customer claims and potential customs penalties. Knowledge Gap Despite the operational risks, structured risk prioritization and systematic error-prevention mechanisms in bonded warehouse contexts remain insufficiently documented. Aims This study aims to identify, prioritize, and mitigate operational errors in receiving and picking activities using Failure Mode and Effect Analysis and Poka Yoke. Results The analysis reveals that the highest risk in receiving arises from failure to inspect sampling goods across different raw material types, while incorrect item retrieval constitutes the most critical risk in picking, both indicated by elevated Risk Priority Number values. Novelty This study integrates FMEA-based risk prioritization with control and warning-based Poka Yoke mechanisms specifically tailored to bonded warehouse operations. Implications The proposed revisions to work instructions, automated barcode input, pick-to-light systems, and priority rack arrangements provide a structured approach to reducing recurring errors, supporting customs compliance, and strengthening warehouse reliability within bonded logistics environments. Highlights: Critical risks were concentrated in inspection omissions and order retrieval mismatches. Risk Priority Number analysis enabled clear prioritization of operational failures. Preventive mechanisms combined procedural controls with visual warning systems. Keywords: FMEA, Picking, Poka Yoke, Receiving, Risk Mitigation